AIE active piperazine appended naphthalimide-BODIPYs: photophysical properties and applications in live cell lysosomal tracking. Issue 1 (8th November 2018) - Dwivedi, Bhupendra Kumar; Singh, Roop Shikha; Ali, Afsar; Sharma, Vinay; Mobin, Shaikh M.; Pandey, Daya Shankar
Abstract : Piperazine appended naphthalimide-BODIPYs (NPB1–NPB4 ) exhibiting solvatochromism, aggregation-induced emission, and high selectivity towards lysosomal pH in living cells have been described. Abstract : Piperazine appended naphthalimide-BODIPYs (NPB1–NPB4 ) exhibiting solvatochromism and aggregation-induced emission with a large Stokes shift (up to 146 nm) have been described. Separation of naphthalimide and BODIPY fluorophores by piperazine in these conjugates creates a donor–acceptor system and induces twisted intramolecular charge transfer, in addition to photoinduced electron transfer. The crucial role of naphthalimide, the alkyl chain length, the piperazine ring, and the solid-state packing on AIE has been extensively investigated by various studies. Superior cell permeability coupled with bio-compatibility of these conjugates offers a unique opportunity for their potential applications in live cell lysosomal tracking.